AN APPROPRIATE BUSINESS STRATEGY FOR SMALL MEDIUM ENTREPRISES: A CASE STUDY OF PIKSEL INDONESIA (Malaysian Management Journal, 2019)
The aim of the study is to establish the most appropriate business strategy for Piksel Indonesia which is a creative company focusing on technology and fashion designs, resulting from the batik consumption preferences while planning to use batik products. Data from 338 respondents were randomly collected from several cities in Indonesia. The first section deals with the demographic background of the respondents, and the remaining of the questions deal with the respondents’ impulse towards batik products. The survey results show differences in previous studies. The first difference is the source of information about batik products obtained by the customer. Secondly, the study by the researchers builds on the consumer’s tastes about the batik style and the results are 54.6 percent. Integrated cost leadership/differentiation is Piksel Indonesia’s best business strategy. For Batik Fractal, their batik products brand, low cost was achieved by employing their vendor to produce the product from the minimum overhead. The production flow begins with the order of the customer that the pattern, colour, material and size chart have been determined. JBatik, which is a parametric software to make a new and distinguish batik pattern established by Piksel Indonesia, has no direct competitors at present. As with Batik Fractal, integrated cost management/differentiation strategy is the best strategy.